Plant Science View on Biohybrid Development - Skrzypczak, Tomasz; Krela, Rafał; Kwiatkowski, Wojciech; Wadurkar, Shraddha; Smoczyńska, Aleksandra; Wojtaszek, Przemysław (Frontiers in Bioengineering and Biotechnology, 2017)
Bio-hybrid consists of a living organism or cell and at least one engineered component. Designing robot-plant bio-hybrids is a great challenge: it requires interdisciplinary reconsideration of capabilities intimate specific to the biology of plants. Envisioned advances should improve agricultural/horticultural/social practice and could open new directions in utilization of plants by humans. Proper bio-hybrid co-operation depends upon effective communication. During evolution, plants developed many ways to communicate with each other, with animals, and with microorganisms. The most notable examples are: the use of phytohormones, rapid long-distance signaling, gravity and light perception. These processes can now be intentionally re-shaped to establish plant-robot communication. In this article, we focus on plants physiological and molecular processes that could be used in bio-hybrids. We show phototropism and biomechanics as promising ways of effective communication, resulting in an alteration in plant architecture, and discuss the specifics of plants anatomy, physiology and development with regards to the bio-hybrids. Moreover, we discuss ways how robots could influence plants growth and development and present aims, ideas and realized projects of plant-robot bio-hybrids.